The Role of International Organizations in Shaping the Educational Policy for Higher Education and the First Historically Identified Evaluation Efforts of the Greek Academy of Somatic Education, in the 20th Century (Journal of Education and Development, 2023)
This paper focuses on the presentation of data which are related on the one hand to the role of International Organizations in shaping the educational policy for Higher Education (with an emphasis on Physical Education and Sports Sciences) and on the other hand to the first historically identified efforts to evaluate a higher education institution of Physical Education and Sports Sciences in Greece. Official texts and reports of International Organizations such as International Council on Health, Physical Education and Recreation, United Nations Educational, Scientific and Cultural Organization, and Council of Europe were studied for the period 1950-1970, according to which their important role and influence in the shaping of educational policy both in Greece and in many other countries was revealed. Regarding the formulation of the educational policy for Higher Education in Greece, the results of the research demonstrate the role that International Organizations played in the initial evaluation efforts concerning the National Academy of Somatic Education which was the only public tertiary education institution for Physical Education and Sports Sciences in Greece at the time and which subsequently was upgraded into the School of Physical Education and Sports Sciences in the National and Kapodistrian University of Athens.